Early Maladaptive Schemas in the Patients with Somatoform Disorders - Ýsmet Kýrpýnar; Erdem Deveci; Demet Zihni Çamur; Alperen Kýlýç (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Somatoform disorders are characterized by physical symptoms that suggest a medical condition but that are not fully explained by a medical condition. A number of studies have suggested the efficacy of cognitive behavioral therapy for somatoform disorders. But, while it is clear that somatoform disorders are closely related to a number of cognitive factors, the precise nature of these relationships have not been elucidated yet. The aim of the present study was to determine the relationships between DSM-IV hypochondriasis and somatoform disorder diagnoses and the early maladaptive schemas which have been proposed by Young as the core of psychological problems. Method: We investigated a total of 28 patients aged 18-65 years, were diagnosed as Hypochondriasis or Somatization Disorder according to DSM-IV and 30 healthy controls. All participitans were assessed with The Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-1). Data were obtained by using a Sociodemographic Questionnaire and Young Schema Questionnaire-Short Form 3.